Satisfaction levels of clients using emergency medical service in Klang Valley: retrospective telephone survey - Nurumal, Mohd. Said; Raja Lexshimi, RG; Che Jamaludin, Farrah Ilyani; Sheikh Ab Karim, Sarah (UKM, 2016)
The measurement of clients' satisfaction with pre-hospital care setting is particularly important since Emergency Medical Service (EMS) is often a primary determinant in the health care delivery service and there is no information available regarding this variable in Klang Valley, Malaysia. This study aims to identify the satisfaction level of clients using EMS in the Klang Valley region, Malaysia. A retrospective telephone survey (5-7 min/call) was conducted at central and suburbs of Klang Valley’s Medical Emergency Coordinator Centre (MECC). Customer satisfaction was assessed during the period of 1.1.2011 to 31.12.2011 using a structured questionnaire. The total sample size was n=500 patients or significant others. Cases were contacted for this survey by using proportionate stratified random sampling. The survey instrument was designed to assess two primary domains of satisfaction which are 1) interaction and 2) communication, in addition to overall satisfaction. The urban versus suburban and views on the different types of cases were compared. In this study 100 patients and 400 significant others participated. Customer satisfaction mean score was 3.12±0.88 in a 1- 5 scale. This study indicated that both urban and suburban society in the Klang Valley areas were satisfied with the pre-hospital care service they received. There are many other external factors that can affect the satisfaction of the customer such as a technical error or bad weather. All these could delay a response. Evaluating customer satisfaction is an essential indicator for improving and achieving an excellent health care delivery system for a society. Keyword: Emergency Medical Service, Satisfaction, Telephone Survey